Developing Research Managers and Leaders through Management Development Programme in National Agricultural Research and Education System in India - Alok Kumar; R. V. S. Rao, P. Ramesh, K. H. Rao, Ch. Srinivasa Rao (Indian Journal of Extension Education, 2022)
To develop research managers and leaders in NARES, it is substantially important to enable existing and proposed managers to expand their understanding of the principles, techniques and approaches involved in management. To achieve this goal, ICAR-NAARM, offered a course “Management Development Programme on Leadership Development” for more than one decade. To assess and evaluate the performance of the participants in their respective institutions, the respondents and their reporting officers interviewed to determine whether programme has produced the desired effect. A total of 150 respondents and their reporting officers gave their views for this study. Based upon mean score and standard deviation, most of the respondents were average (62.67%), below average (19.33%) and above average (18%) before training, knowledge levels after training indicated, most of the respondents were average (66%), below average (17.33%) and above average (16.66%) whereas changes in knowledge levels indicated that, most of the respondents having average (63.33%), below average (18.66%) and above average (18%). For Behaviour, feedback received from the participants after 6 months and more period and the overall satisfaction level was around 3.89 out of 5.0, whereas overall results was around 3.42 out of 5.0.